2017
DOI: 10.1016/j.aninu.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of growth rate, body lipid, moisture, and energy models for white sturgeon ( Acipenser transmontanus ) fed at various feeding rates

Abstract: The objectives were to develop and evaluate: 1) growth rate models, 2) body lipid, moisture, and energy models for white sturgeon fed at various feeding rates (FR; % body weight [BW] per day) and then evaluate responses at proportions of optimum feeding rate (OFR) across increasing BW (g). For objective 1, 19 datasets from the literature containing initial BW, FR and specific growth rate (SGR; % BW increase per day) were used. For objective 2, 12 datasets from the literature (11 from objective 1) containing SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This can be comparable to results reported in other fish species such as white sturgeon ( Acipenser transmontanus ; Hung & Lutes, ; De Riu et al, ), green sturgeon ( A. medirostris ; Zheng, Deng, De Riu, Moniello, & Hung, ), lake sturgeon ( A. fulvescens ; Lee, Zhao, et al, ), striped bass (Hung et al, ) and grass carp ( Ctenopharyngodon idellus ; Li et al, ). Because body weight changes are highly associated with nutrient gains or losses (Dumas, de Lange, Farance, & Bureau, ; Lee, Sonmez, Hung, & Fadel, ), the increased protein and lipid gains as the feeding rate increased were in line with what the growth responses were observed in both of the trials.…”
Section: Resultssupporting
confidence: 55%
“…This can be comparable to results reported in other fish species such as white sturgeon ( Acipenser transmontanus ; Hung & Lutes, ; De Riu et al, ), green sturgeon ( A. medirostris ; Zheng, Deng, De Riu, Moniello, & Hung, ), lake sturgeon ( A. fulvescens ; Lee, Zhao, et al, ), striped bass (Hung et al, ) and grass carp ( Ctenopharyngodon idellus ; Li et al, ). Because body weight changes are highly associated with nutrient gains or losses (Dumas, de Lange, Farance, & Bureau, ; Lee, Sonmez, Hung, & Fadel, ), the increased protein and lipid gains as the feeding rate increased were in line with what the growth responses were observed in both of the trials.…”
Section: Resultssupporting
confidence: 55%
“…Because growth is closely correlated with nutrient accumulation in fish body (Dumas, Lange, France, & Breau, ; Lee, Sonmez, Hung, & Fadel, ), the pattern of change in the protein and lipid contents of the flounder responding to the graded choline levels was in line with what the growth response exhibited. This is in agreement, in part, with previous results reported in white sturgeon (Hung, ), yellow perch (Twibell & Brown, ) and grouper (Qin et al, ), exhibiting that the whole‐body fat content was responsive to the respective dietary choline level.…”
Section: Resultsmentioning
confidence: 74%
“…This has led to an increase in the pressure of food competition and, as a result, to a decrease in the output of young sturgeon growing up. At the same time, it was shown that with an increase in the growing period, moisture in sturgeon muscles decreases and fat and protein increase (Poleksic et al, 2010;Memis et al, 2011;Kairullaev et al, 2017;Lee et al, 2017). Corresponding age-related changes have been studied in other fish species (Volichenko et al, 2017;Payuta & Flerova, 2020).…”
Section: Discussionmentioning
confidence: 98%